In vitro susceptibility of Cuban Aspergillus spp. strains of clinical and environmental origin - Javier L. San Juan; Carlos M. Fernández; Michel Almaguer; Mayda R. Perurena; Gerardo F. Martínez; Rosario E. Velar; María T. Illnait (Biomédica: revista del Instituto Nacional de Salud, 2017)
Introduction: The behavior of antifungal susceptibility of Aspergillus spp. in Cuba remains unknown. The antifungals recommended to treat aspergillosis are amphotericin B, itraconazole, voriconazole and echinocandins. The influence of the environment may set off the emergence of drug-resistance in these microorganisms. Objective: To evaluate in vitro susceptibility of Aspergillus spp. strains to amphotericin B, itraconazole and voriconazol, and the relationship between susceptibility patterns and their origin. Materials and methods: Minimum inhibitory concentrations of amphotericin B, itraconazole and voriconazole were determined for 60 Aspergillus spp. strains of clinical and environmental origin using the M38-A2 method of the Clinical and Laboratory Standards Institute. Results: We found 21 amphotericin B resistant strains (mainly from clinical samples and hospital environments), as well as three itraconazole resistant strains (from non-hospital outdoor and indoor environments). No voriconazole resistance was found. No relationship was found between strain origin and susceptibility. Conclusions: Results suggest the possible existence of environmental factors or interactions with resistant genotypes which may give rise to resistant phenotypes in our country. This is the first report of in vitro  Aspergillus spp. resistant strains in Cuba. These studies should be broadened and include molecular and phylogenetic analyses.